Asprosin, a novel glucogenic adipokine: a potential therapeutic implication in diabetes mellitus - Hekim, Munevver Gizem; Kelestemur, Muhammed Mirac; Bulmus, Funda Gulcu; Bilgin, Batuhan; Bulut, Ferah; Gokdere, Ebru; Ozcan, Mete (Taylor & Francis Ltd, 2023)
Objectives We aimed to investigate the effects of asprosin on diabetes with a focus on serum glucose, irisin, ghrelin, leptin levels and hepatic levels of triglycerides (TG), cholesterol, low-density lipoprotein (LDL). Methods Asprosin (10 mu g/kg) was administered intraperitoneally four times at 3-day intervals and then blood and hepatic parameters above mentioned were investigated in control and diabetic mice. Results The administration of asprosin increased blood glucose level in healthy animals (p = .05) whereas it did not change blood glucose level in diabetic animals. In addition, while asprosin decreased irisin level and increased ghrelin level, it did not change leptin level in diabetic mice. Therewithal, asprosin decreased the increasing levels in hepatic TG, cholesterol, and LDL in diabetic mice. Conclusions Our novel findings implicate that asprosin may be a target molecule in preventing the development and complications of diabetes.
Keywords: Asprosin; diabetes mellitus; blood glucose; irisin; ghrelin